Question #1aa2d

1 Answer
Apr 27, 2017

x^2+y^2=((x^2-y^2)/(x^2+y^2))^2

Explanation:

Here is the graph of the original equation r = cos(2theta):

![Desmos.com](useruploads.socratic.org)

Use the identity cos(2theta) = cos^2(theta)-sin^2(theta)

r = cos^2(theta)-sin^2(theta):

Substitute the sqrt(x^2+y^2) for r, x^2/(x^2+y^2) for cos^2(theta), and y^2/(x^2+y^2) for sin^2(theta):

sqrt(x^2+y^2)=x^2/(x^2+y^2)-y^2/(x^2+y^2)

sqrt(x^2+y^2)=(x^2-y^2)/(x^2+y^2)

Here is the graph of that equation:

graph{sqrt(x^2+y^2)=x^2/(x^2+y^2)-y^2/(x^2+y^2) [-10, 10, -5, 5]}

It is only half of the loops

Square both sides:

x^2+y^2=((x^2-y^2)/(x^2+y^2))^2

Here is the graph of that equation:

graph{x^2+y^2=((x^2-y^2)/(x^2+y^2))^2 [-10, 10, -5, 5]}

This looks like the polar equation.